DEVELOPMENT OF STUDENT WORKSHEET BASED ON THE PBL MODEL TO IMPROVE CRITICAL THINKING SKILL IN PHASE C - Fatkhur Rohman; Mia Azzahra; Pramudiyanti Pramudiyanti; Joko Supriono; Romlah Romlah; Fitriyani Fitriyani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Critical thinking skills are the abilities that students need to have in the 21st century. When students have critical thinking skills, they are expected to be able to seriously understand, analyze, and process information before making decisions. The purpose of this research is to improve students' critical thinking skills through PBL-based worksheets on the subject of the human digestive system. This LKPD product was developed using the ADDIE model, which was tested at MIN 2 West Lampung. As many as 15 students were in the control class, and 25 students were in the experimental class. The results of this study indicate that the validated LKPD based on the validity test analysis using Aiken yielded a score of 0.8210 in the valid category. The analysis of the practicality test for educators resulted in 85% and 88% of students being in the very practical category, respectively. The product effectiveness analysis resulted in an average pre-test score of 58.4 and an average post-test score of 83.2. The development of worksheets based on the PBL model had a significant influence on students' critical thinking skills.